Molecular phylogeny and historical biogeography of marine palaemonid shrimps (Palaemonidae: Palaemonella-Cuapetes group) - Frolová, Pavlína; Horká, Ivona; Ďuriš, Zdeněk (Scientific reports, 2022)
Palaemonidae is the most speciose shrimp family within the infraorder Caridea, composed predominately of freshwater species and marine symbiotic species. The subject of this study is a clade of mainly free-living marine taxa representing a basally separated lineage from most of the symbiotic marine palaemonid genera. Phylogenetic and biogeographic relationships were explored by analysing sequence data from two mitochondrial and four nuclear markers. Maximum likelihood and Bayesian analyses, based on sequences from 52 species of 11 genera, provided similar tree topologies revealing the genera Palaemonella, Cuapetes and Eupontonia as non-monophyletic groups. Divergence time and S-DIVA analyses reveals that the focal clade originated during the Late Cretaceous in the Paleotethys region respective to the present Indo-West Pacific area, a minor part of which spread out to the eastern Pacific during the Paleocene, followed by further migration into the Atlantic (before the closure of the Panama Isthmus). The ancestral state reconstruction of host associations revealed eight independent symbiotic lineages originating from free-living ancestors, entering primary symbioses. The first associations with Cnidaria are estimated to have evolved in the Eocene. This study points to the need of taxonomic revisions of the non-monophyletic genera concerned.
Keywords: Animals; Phylogeny; Bayesova věta; symbióza; zvířata; Palaemonidae; fylogeneze; Decapoda (Crustacea); Bayes Theorem; Decapoda; Symbiosis